ANALISIS PENGARUH PENGELUARAN PEMERINTAH UNTUK SEKTOR PERTANIAN TERHADAP PDRB SEKTOR PERTANIAN 35 KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2007-2010 - Suwanti, Suwanti; Agung Gunanto, Edy Yusuf (Diponegoro Journal of Economics, 2013)
The agricultural sector is the dominant sector in Central Java, but the lack of government's role in the sector. This study aimed to analyze the effect of government spending and other factors that may affect the agricultural sector GDP.             This study uses secondary data analysis tools to approach the data panel Fixed Effect Model (FEM) or the Least Square Dummy Variable (lSDV) model, which consists of the data during the period 2007-2010 times series and cross section data 35 regency / cities in Central Java.             Results of this study indicate that the agricultural sector of government spending positive and significant effect on the agricultural sector PDRB, labor and a significant positive effect on the agricultural sector PDRB. Direction of positive regression coefficient indicates that government spending, labor may lead to an increase in agricultural PDRB.